ESKALASI KONFLIK KELUARGA DALAM DINAMIKA GLOBALISASI DAN PENDEKATAN RESOLUSI BERBASIS FIKIH - Muhsan Syarafuddin; Ashari, Winning Son; Siti Nazla Raihana (Al-Majaalis : Jurnal Dirasat Islamiyah, 2024)
In the era of globalization, the escalation of family conflict occurs significantly in various variations and impacts, ranging from divorce to physical and psychological violence even murder. This requires seriousness in finding the right resolution in order to maintain family resilience. This research becomes very important to reveal the right resolution by referring to fiqh-based resolution because fiqh itself is used as a legal framework rooted in Islamic teachings that are relevant in resolving conflicts in the family context. Researchers used a literature review with a qualitative approach to analyze various literature sources related to family conflicts and their resolution. The results showed that the escalation of conflict in the global era with its various variants found its resolution by understanding and applying the principles of fiqh-based resolution in the form of holistic Islamic teachings. The real implication of fiqh-based resolution is that it helps build a harmonious and mutually supportive family environment and is key to resolving family conflicts effectively and sustainably.